Pengelolaan Edu-Wisata Lontar Sewu Dalam Upaya Meningkatkan Pendapatan Asli Daerah Di Tingkat Desa Hendrosari Kecamatan Menganti Kabupaten Gresik - Hanan Titis Hidayat; Evi Silvia Melina; Galuh Pratama (Universitas Mbojo Bima, 2025)
Abstract Village tourism is one of the village efforts in managing the village’s potential. Lontar sewu edu-tourism is one of the business units of the Village-Owned Enterprise (BUMDes) in Hendrosari village, Menganti district, Gresik Regency, which has succeeded in improving the community’s economy through villafe tourism development. The purpose of this study was to determine the management of lontar sewe edu-tourism which influences the increase in village incove. This study used a qualitative approach with descriptive methods. Data were collected through interviews, observation, and documentation. The collected data were then processed and analyzed using qualitative data analysis techniques. This results indicates that lontar sewu edu-tourism village has a significant impact on increasing village income by empowering the local village community. This has an impact on reducing unemployment and increasing the original regional income of Hendrosari village.